2006
DOI: 10.1103/physrevb.74.165306
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy investigation of segregation and critical floating-layer content of indium for island formation inInxGa1xAs

Abstract: We have investigated InGaAs layers grown by molecular-beam epitaxy on GaAs (001) -1 -

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…This also implies that the kinetic model is also accurate only for x Ͻ 0.11, at least for high temperatures, when the thermodynamic and kinetic models are equivalent. The exchange model was shown to give a very good agreement with experimental transmission electron microscopy data on In rich ͑25%͒ InGaAs layers by Litvinov et al 78 Furthermore the authors show how the agreement is substantially improved compared to using the kinetic model, a result that confirm the earlier conclusions of Gerard et al 42 The three-layer model is predicting a substantial delay in the incorporation of In in the early stages of the growth of the QW and also a more pronounced tail of In segregated into the upper GaAs layer. Godbey and Ancona 75 noticed that such increased tail is more in agreement with experimental data on SiGe structures.…”
Section: ͑12͒supporting
confidence: 59%
“…This also implies that the kinetic model is also accurate only for x Ͻ 0.11, at least for high temperatures, when the thermodynamic and kinetic models are equivalent. The exchange model was shown to give a very good agreement with experimental transmission electron microscopy data on In rich ͑25%͒ InGaAs layers by Litvinov et al 78 Furthermore the authors show how the agreement is substantially improved compared to using the kinetic model, a result that confirm the earlier conclusions of Gerard et al 42 The three-layer model is predicting a substantial delay in the incorporation of In in the early stages of the growth of the QW and also a more pronounced tail of In segregated into the upper GaAs layer. Godbey and Ancona 75 noticed that such increased tail is more in agreement with experimental data on SiGe structures.…”
Section: ͑12͒supporting
confidence: 59%
“…Below x = 0.25 the critical surface composition cannot be reached, which prevents QD formation. In a later study [61,62], it was found that the measured segregation profile could be better explained by a different model by Muraki et al [63], and that the critical surface layer to attain 3D nucleation is about 1.1 ML InAs.…”
Section: Uncapped Ingaas/gaasmentioning
confidence: 95%
“…In the literature, these floating indium atoms were generally assumed to be produced by surface segregation, which may result from three main driving forces: i) relative surface stress, ii) chemical interactions, and iii) size mismatch. For example, Muraki et al [312] demonstrated that because of surface segregation of indium on the growth surface of an In x Ga 1−x As alloy, the surface chemical composition may reach the point x > 1, which is possible only when excess indium is floating on the surface [313] instead of chemically bonded to it. Garcia et al [314], by in-situ measurements of the epitaxial stress, experimentally demonstrated that only 50% of the indium could be incorporated into the lattice after 2.3 ML of InAs were deposited on the GaAs(001) substrate.…”
Section: Indium Floatingmentioning
confidence: 99%